International Marketing of Icelandic Salmon Rivers. The experience of fishing outfitters - Þorgils Helgason 1987- (2014)
This thesis examines the experience of fishing license outfitters in Iceland on marketing strategies. It provides new knowledge of ways of marketing for angling destination and what directions to take to get ahead of other destinations. The thesis is based on qualitative methods that were judged effective means to gather data from the small and tight community of the Icelandic angling industry. For this thesis six individual in depth interviews with experienced outfitters were conducted. The goal being to explore and use their experience to figure out how Icelandic salmon rivers are marketed. It investigates what factors impact the marketing environment and implies positive ways of improvement. The main findings show bright points in the current marketing situation of Icelandic rivers, but the environment appears to be fragmented. There are clear ways to improve the marketing with better coordinated messages and friendlier framework. The infrastructure in Iceland is good, according to participants, but the united opinion is that there is a demand for better structure with the services of guides. Participants agreed that Iceland has a positive image that helps attract customers. Pricing effects is an interesting subject and most participants talked about the prices simply being too high. The project this thesis is based on is part of a larger project titled Salmonchange, hosted by the Norwegian University of Life Sciences, which focuses on sustainable development and innovation in angling.